FOREST SCHOOL AND ENCOURAGING POSITIVE BEHAVIOUR : Outdoor Education Skills for Pupils with Additional or Complex Needs - Rylance, David (Jessica Kingsley Publishers, 2022)
"An interesting and innovative look at forest school practices, which ties in well with our special education titles, this book shows how to use forest school to help children with challenging behaviour by sharing practical skills, techniques and activities. The book explains strategies and approaches for forest school leaders and education professionals to use in outdoor settings, and expands on explanations of activities to show how leaders can adapt them to suit their particular setting. This means there is a possibility it could be used by mainstream and SEND school staff as well as independent outdoor education/forest school practitioners"--